Influence of Sputtering Power Density on the Thermoelectric and Mechanical Properties of Flexible Thermoelectric Antimony Telluride Films Deposited by DC Magnetron Sputtering - Junlabhut, Prasopporn; Nuthongkum, Pilaipon; Sakdanuphab, Rachsak; Harnwunggmoung, Adul; Sakulkalavek, Aparporn (My University, 2020)
Antimony telluride (Sb2Te3) films were deposited on flexible polyimide substrates by DC magnetron sputtering technique using a 99.9% alloy Sb2Te3 target. We measured structural, electrical, thermoelectric and mechanical properties with sputtering power density in the range 30–50 W. X-ray diffraction confirmed that all Sb2Te3 films have high crystallinity with a significant preferential growth along the (015) plane. Surface morphologies were verified by scanning electron microscope: deposited film grain size increased with sputtering power density. The elemental composition was determined by energy dispersive x-ray spectroscopy. Electrical transport properties, carrier concentration, was measured by Hall effect measurement at room temperature. Electrical conductivity and Seebeck coefficient were simultaneously measured by a DC four-terminal method (ZEM-3). The power factor was strongly dominated by electrical conductivity, leading to a maximum of 1.95 mW/K2m with sputtering power 45 W at 300°C. The wettability test, based on the contact angle, evaluated surface energy and hydrophilicity. Nanoindentation was measured on a NHT2 CSM Instrument with diamond Berkovich indenter (B-P 31) at room temperature. The hardness and elastic modulus of deposited Sb2Te3 films increased with the power density.
Keywords: antimony telluride; DC magnetron sputtering; Flexible thermoelectric; sputtering power density